Legal Politics and Presidential Lawmaking: Balancing Powers to Realize State Objectives - Fitryantica, Agnes; Fitri, Rizki Rahayu (Journal of Constitutional and Governance Studies, 2025)
Legal politics plays a pivotal role in the formation of legislation proposed by the President in Indonesia, particularly in aligning lawmaking with the constitutional goals of the state. As the highest executive authority, the President functions not only as an implementer of laws but also as an initiator of legal reforms aimed at addressing pressing societal needs. This study investigates the extent to which legal politics influences presidential legislative initiatives and how such initiatives contribute to realizing the state’s goals within the framework of the rule of law and democratic governance. Utilizing a qualitative and normative legal research approach, this paper examines the interaction between political interests, legal authority, and legislative responsiveness. The study finds that inclusive and participatory legal politics is essential for ensuring that legislation is democratic, transparent, and responsive to public aspirations. It highlights the importance of aligning presidential legislative initiatives with the principles of legal accountability, public participation, and institutional balance. Moreover, the research underscores the need to bridge the gap between presidential visions and practical law enforcement, particularly concerning the effectiveness of laws in recovering state losses and achieving justice. Ultimately, strengthening checks and balances in the legislative process initiated by the President is crucial for preserving the integrity of Indonesia’s legal system and upholding democratic values.